The Influence Of Digital Literature In The Society 5.0 Era On Improving Digital Literacy and Reading Interest: A Literature Review - Alya Alya (Yayasan Nurul Iman Muara Gading Mas, 2025)
The role of digital Literature in increasing literacy and reading interest has now become a crucial instrument in the era of technological transformation. However, most prior studies still fokus on basic techological mastery, leaving a gap in research regarding how digital literature integrates cyber proficiency with humanistic values in the Society 5.0 era. This study aims to analyze the influence of digital literature on enhancing digital literacy and reading interest by aligning technological, ethical, and aesthetic aspects. The method used is a literature review analyzing ten scientific articles relevant to literature learning, creative media (poetry, short stories, novels), and the Society 5.0 ecosystem. The data synthesis results indicate that the utilization of digital literature and e-learning innovations significantly boosts reading interest and stimulates the creative processes of the younger generation. Concurrently, Navigating and appreciating cyber works sharpen readers’ digital literacy skills while contextually internalizing character values, ethics, and aesthetics. In conclusion, digital literature in the Society 5.0 era effectively functions as a dual medium that not only hones technological skills but also preserves the humanistic values of readers.